2020
DOI: 10.1007/s00405-020-06311-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the nasal bacterial microbiome diversity of allergic rhinitis, chronic rhinosinusitis and control subjects

Abstract: Purpose Until now, the microbiome of the nasal cavity and its contribution to nasal mucosal disease has remained poorly understood. The advent of cultivation-free molecular methods makes it possible to characterize the total microbiome of the nasal cavity. We sought to assess the microbial diversity and composition of the middle meatus in allergic rhinitis (AR) patients, chronic rhinosinusitis patients without polyps (CRSsNP) and a control population to determine the microbiota associated with the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…In our recent microbiome comparison study between healthy controls and CRS patients, various genera of the Lactobacillaceae including Lactiplantibacillus, Latilactobacillus and Lacticaseibacillus were also found to be more prevalent and abundant in healthy controls compared with CRS patients (De Boeck et al, 2019) (Figure 1). Similarly, a lower abundance of lactobacilli was recently reported within the nasal microbiome of AR patients compared with healthy controls (Gan et al, 2020). Compared with other human body sites, such as the vagina (Petrova et al, 2015) and the gastrointestinal tract (Heeney et al, 2018), the abundances of lactobacilli in the URT (Abreu et al, 2012;Ling et al, 2013;Stearns et al, 2015;, are much lower (Figure 1).…”
Section: Lactic Acid Bacteria Have a Habitat In The Respiratory Tractmentioning
confidence: 52%
See 1 more Smart Citation
“…In our recent microbiome comparison study between healthy controls and CRS patients, various genera of the Lactobacillaceae including Lactiplantibacillus, Latilactobacillus and Lacticaseibacillus were also found to be more prevalent and abundant in healthy controls compared with CRS patients (De Boeck et al, 2019) (Figure 1). Similarly, a lower abundance of lactobacilli was recently reported within the nasal microbiome of AR patients compared with healthy controls (Gan et al, 2020). Compared with other human body sites, such as the vagina (Petrova et al, 2015) and the gastrointestinal tract (Heeney et al, 2018), the abundances of lactobacilli in the URT (Abreu et al, 2012;Ling et al, 2013;Stearns et al, 2015;, are much lower (Figure 1).…”
Section: Lactic Acid Bacteria Have a Habitat In The Respiratory Tractmentioning
confidence: 52%
“…Mean relative abundances of Dolosigranulum (red bars) and Lactobacillaceae (blue bars) as part of the microbiome in different human body habitats. Based on our research (De and available literature(Laufer et al, 2011; Biesbroek et al, 2014a;Stearns et al, 2015;Hasegawa et al, 2017;Gan et al, 2020), Dolosigranulum and Lactobacillus are proposed as indicator taxa for health. Using the curatedMetagenomicData R-package based on publicly available shotgun sequencing data data(Pasolli et al, 2017), their mean relative abundances were calculated in the URT, skin, gut and vagina.…”
mentioning
confidence: 92%
“…Similarly, the diversity of nasal microbiota decreases in other pathogenic conditions, such as chronic rhinosinusitis (CRS) with or without nasal polyp (19,20) . However, one study found no difference in microbiome diversity among control, allergic rhinitis, and CRS without nasal polyp patients (21) . Instead, allergic rhinitis patients had a higher abundance of Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes and a lower abundance of Lactobacillus than control group individuals (21) .…”
Section: Microbiotamentioning
confidence: 99%
“…However, one study found no difference in microbiome diversity among control, allergic rhinitis, and CRS without nasal polyp patients (21) . Instead, allergic rhinitis patients had a higher abundance of Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes and a lower abundance of Lactobacillus than control group individuals (21) . Haemophilus was more abundant in the CRS patients than in the controls or allergic rhinitis patients (21) .…”
Section: Microbiotamentioning
confidence: 99%
“…Among the URT commensal bacterial species that have gained interest as potential next-generation probiotics, Dolosigranulum pigrum is one of the most promising to beneficially influence human respiratory health. It was observed that this Gram-positive, catalase-negative Firmicute bacterium is abundant in healthy URT, reaching a relative abundance of up to 50% [ 15 ], and different studies have related it to vaginal delivery and breastfeeding [ 16 ]. A lower incidence of URT infections and a reduced probability of contracting bronchiolitis were observed in children who had higher numbers of D. pigrum in their respiratory microbiota [ 17 ].…”
Section: Introductionmentioning
confidence: 99%